2021
DOI: 10.1108/jhti-10-2020-0199
|View full text |Cite
|
Sign up to set email alerts
|

Crisis preparedness of hospitality managers: evidence from Malaysia

Abstract: PurposeCrisis planning and improvements to business resilience are increasingly significant aspects of hotel management. This study investigates the crisis preparation of hotel managers in Malaysia and how their perceptions affect crisis planning and preparation.Design/methodology/approachA qualitative research method of semi-structured interviews with 24 hospitality managers in Malaysia was conducted. Data were analysed thematically using ATLAS.ti software, version 8.FindingsThe findings showed that crisis pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 79 publications
2
37
1
1
Order By: Relevance
“…The study identified relevant dimensions of employer responsibilities such as safety assurance and of employee duties such as personal protection. Ghaderi et al (2021) studied the crisis preparedness among Malaysian hotel managers. The qualitative study uncovers that the hotel managers were not well prepared to manage crisis and that the organizational culture has a great influence on the crisis preparation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The study identified relevant dimensions of employer responsibilities such as safety assurance and of employee duties such as personal protection. Ghaderi et al (2021) studied the crisis preparedness among Malaysian hotel managers. The qualitative study uncovers that the hotel managers were not well prepared to manage crisis and that the organizational culture has a great influence on the crisis preparation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Understanding each other's changing needs and reactions can encourage a fruitful relationship between FSBs and their consumers (Darvishmotevali et al, 2020), especially during the pandemic. Additionally, having a culture of mindful preparation can prepare FSBs to withstand the crisis (Ghaderi et al, 2021).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…By undertaking the review during the crisis (Lai and Wong, 2020), this paper focused on a sustainable solution to benefit stakeholders. First, although Pforr and Hosie (2008) suggested managers take precautions by focusing on the pre-crisis phase, the supply chain crisis during COVID-19 illustrated that managers believed in reactive rather than proactive crisis management (Ghaderi et al, 2021;Yacoub and ElHajjar, 2021). FSBs needed to understand the nature of the crisis in the pre-crisis phase to address any lack of preparedness (Ritter and Pedersen, 2020).…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, destinations that want to divert away from poverty perceptions may focus on the second solution that is oriented on destination aspects, which act as pull factors in the tourist decision-making process. According to Ghaderi et al (2021), service challenges during crises mainly originate from factors related to people and external conditions. Therefore, attempts to shift attention away from poverty may consider the enhancement of service-related aspects in hospitality and tourism.…”
Section: Managerial Implicationsmentioning
confidence: 99%